Unexpected consequences: A case of ketamine-induced seizure in procedural sedation - Adem Az; Yunus Doğan (Turkish Journal of Emergency Medicine)
This case report describes a 32-year-old male who underwent ketamine procedural sedation and experienced a generalized tonic–clonic seizure. Despite its rapid onset and favorable tolerance profile, this case emphasizes the potential convulsive side effects of ketamine, which is commonly used for procedural sedation. While ketamine has shown promise in treating acute pain, refractory status epilepticus, and treatment-resistant depression and schizophrenia, it is associated with side effects such as hallucinations, visual disturbances, dizziness, nausea, and vomiting. The patient in this case received a carefully titrated dose of 40 mg of ketamine intravenously and underwent successful shoulder reduction while under sedation. However, within 60 s of receiving the ketamine, the patient experienced a 60-s seizure that was stopped with the administration of 5 mg of diazepam intravenously. The patient was hospitalized for further evaluation, including an electroencephalography (EEG) that showed no abnormalities. This case highlights the need for health-care professionals to be aware of the potential convulsive side effects of ketamine and to carefully monitor patients who receive ketamine sedation.